Utilization of Nuisance Parameter to Increase Positioning Accuracy - Michler, Oliver; Khalaf-Allah, Mohamed (European Navigation Conference, ENC 2019, 2019)
In this paper, the accuracy improvement of phase of arrival (POA) based positioning of a tag/receiver is addressed. The linear least-squares estimator introduces a nuisance parameter, which is a function of the tag's position. This nuisance parameter can be utilized to refine position estimation in order to reduce estimation errors. Measurement outliers and spikes will be removed by applying a recursive average filter.The results show that filtering alone can only reduce the maximum error without significantly affecting the mean error. The employment of the nuisance parameter can improve the positioning accuracy significantly with and without measurement filtering. Using the nuisance parameter with unfiltered measurements reduced the mean and maximum positioning errors by 80% and 51% respectively. The best accuracy can be obtained by utilization of the nuisance parameter with the filtered measurements. The achieved mean and maximum errors were 5 mm and less than 3 cm respectively.
Created from Fastlane, Scopus look-up
Keywords: anechoic chamber; linear least-squares; nuisance parameter; phase of arrival (POA); wireless positioning